Estudio de factibilidad para el diseño de campers transportables en el cantón de Baños de Agua Santa, provincia Tungurahua - Solís Solís, Bryan Paúl (2025)
The objective of the present investigation was to determine the feasibility of designing transportable campers for the consumer segment: youth and young adults at canton Baños de Agua Santa- Ecuador, in order to meet the demand in the hotel sector dissatisfied with the current needs of tourists. As The target population was considered to be 125,000 visitors, with a high percentage rate of those of national origin being 79%, while the group of foreigners covers 21% and corresponds to the tourist flow according to MINTUR data. For the methodology a non-experimental transversal mixed-method paradigm was used, which was carried out during the month of February in the year 2022, the scope was descriptive. For data collection, technical tools were used such as: survey, interview and focus group; validated through the analysis of experts in the area in question, later the reliability relationship was calculated with the indicator of Cronbach's Alpha with an equivalent of 0.8; deduced as very reliable, for the statistical sample a margin of error of 6% is calculated, with elements collected during stratified sampling. Based on the results obtained during the investigation it was possible to determine a potential market of 395,000 clients, with a target market of $19,090,350.00 per year. After the budget structure of the GO of $78,349.38; an IRR of 22%; and a discount rate of 15% was considered, with a PRI of 5 years; it was determined as feasible for investment.